Early-onset antibiotic-induced autoimmune hemolytic anemia - Kiblawi, Mahmoud (Ibnosina Journal of Medicine and Biomedical Sciences, 2020)
Drug-induced immune hemolytic anemia (DIIHA) is a rare adverse reaction that causes secondary autoimmune hemolytic anemia in susceptible patients. Drug-induced antibodies and nonimmunological protein absorption are the known mechanisms associated with DIIHA. The two most common reported antibiotics to cause drug dependent antibodies are cephalosporin and penicillin. The author reports two rare cases of DIIHA. The first case is a middle-aged woman clinically diagnosed with community-acquired pneumonia, which develops hemolytic anemia secondary to ceftriaxone. The second case is an elderly gentleman who developed DIIHA secondary to piperacillin–tazobactam that started managing gastrostomy site infection. Both patients had hypoxemia and shortness of breath secondary to drop in hemoglobin, but the outcome was uneventful. Antibiotic-induced hemolytic anemia can develop as early as 2 days after starting the antibiotic. Therefore, early diagnosis and discontinuation of the offending agent can prevent poor prognosis.
Keywords: Autoimmune hemolytic anemia; ceftriaxone; direct antiglobulin test; hemolytic anemia; piperacillin–tazobactam